Preparation method for synchronously generating perovskite quantum dot and silicon dioxide aerogel composite material through color conversion

The SiO2@CsPbBr3 composite material was generated in a one-step process through the synchronous sol-gel method, which solved the problems of perovskite quantum dot stability and uniform distribution, achieved efficient photoelectric performance improvement and simplified process flow, and was suitable for high-performance display devices .

CN119320636APending Publication Date: 2025-01-17MINDU INNOVATION LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323611.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Perovskite quantum dots have poor stability in air, humidity and thermal environments. The traditional preparation methods are complex and time-consuming, making it difficult to ensure uniform distribution and stability of quantum dots.

Method used

The synchronous sol-gel method is used to synchronize the silica aerogel and perovskite quantum dots in a one-step process. By optimizing the drying and heat treatment conditions, SiO2@CsPbBr3 composite material is formed to improve stability and photoelectric properties.

Benefits of technology

It significantly improves the stability and photoelectric properties of quantum dots, extends the service life of materials, simplifies process flow, improves production efficiency and material performance, and is suitable for high-performance flat panel displays and LED fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320636A_ABST
    Figure CN119320636A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for synchronously generating a perovskite quantum dot and silicon dioxide aerogel composite material through color conversion, and relates to the field of quantum dot preparation, and the preparation method comprises the following steps: firstly, dissolving cesium bromide and lead bromide in anhydrous N, N-dimethylformamide, fully stirring, adding oleic acid and aminopropyltriethoxysilane, and stirring to obtain a mixed solution; performing ultrasonic oscillation to obtain a uniform precursor solution; then, mixing TEOS (tetraethyl orthosilicate) and the precursor solution, and stirring while heating to promote sol-gel conversion; adding absolute ethyl alcohol, dropwise adding ammonia water, continuously and fully stirring, and adjusting the pH value to form a uniform homogeneous sol solution; then vacuumizing and circulating nitrogen, adding a cesium oleate solution and continuously stirring to control the perovskite quantum dots to be uniformly generated in a silicon dioxide network, completing sol-gel transformation and forming a stable SiO2 (at) CsPbBr3 composite material; and finally, performing supercritical CO2 drying to finish the formation of silicon dioxide aerogel and the encapsulation of the quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of quantum dot display, and in particular to a composite material of perovskite quantum dots and silicon dioxide aerogel used for synchronously generating color conversion and a preparation method thereof. Background Art

[0002] Perovskite quantum dots are a new type of nanomaterial, consisting of semiconductor crystals with a perovskite structure, and their size is usually between a few nanometers and tens of nanometers. The perovskite structure is a cubic crystal structure with a general chemical formula ABX3, where A and B are two different cations and X is an anion. This structure gives perovskite quantum dots unique physical and chemical properties, making them have a wide range of application potentials in multiple fields.

[0003] Perovskite quantum dots have attracted much attention in the field of optoelectronic devices due to their excellent optoelectronic properties such as high quantum yield, narrow-band luminescence and adjustable luminescence wavelength. However, they have poor stability in air, humidity and thermal environments and are prone to aggregation and degradation. Traditional methods improve their stability through surface modification, doping and composite materials. Among them, silica aerogel has become an ideal quantum dot support material due to its porous structure and high specific surface area. However, traditional preparation methods are complex and time-consuming, and it is difficult to ensure the uniform distribution and stability of quantum dots. Summary of the invention

[0004] In view of the shortcomings of the prior art, the primary purpose of the present invention is to make up for the shortcomings of the prior art and provide a preparation method for color conversion synchronous generation of perovskite quantum dots and silica aerogel composite materials, aiming to combine the sol-gel method with the perovskite quantum dot generation technology, achieve efficient production through synchronous sol-gel synthesis, and achieve the synchronous generation of silica aerogel and perovskite quantum dots in a one-step process, overcome the complex process and stability problems in the prior art, and significantly improve the stability and photoelectric performance of quantum dots. By optimizing the drying and heat treatment conditions, it is ensured that the quantum dots do not fail under high temperature and high pressure, thereby providing a SiO2@CsPbBr3 composite material with high stability and excellent photoelectric performance. The composite material has excellent photoelectric performance, mechanical properties and environmental stability, and is suitable for high-performance flat panel displays, LEDs, QLEDs and other optoelectronic devices.

[0005] To achieve the above object, in a first aspect of the present invention, a method for preparing a composite material of perovskite quantum dots and silica aerogel for synchronous color conversion is provided, the method comprising:

[0006] Step S1, dissolving cesium bromide and lead bromide in anhydrous N,N-dimethylformamide, and stirring until completely dissolved to prepare an initial quantum dot precursor solution; adding oleic acid and aminopropyltriethoxysilane to the initial quantum dot precursor solution, and obtaining a uniform precursor solution by ultrasonic oscillation;

[0007] Step S2, taking tetraethyl orthosilicate (TEOS) as a silicon source, mixing tetraethyl orthosilicate (TEOS) and a precursor solution, and rapidly stirring at the same time to form a preliminary SiO2@CsPbBr3 sol solution; stirring the sol solution at 50°C-70°C for 20min-60min to promote sol-gel transformation; slowly adding anhydrous ethanol, slowly dropping ammonia water and continuing to stir fully, detecting the pH value of the solution in real time, and gradually adjusting the pH to 6.5-7.5 to form a uniform homogeneous sol solution;

[0008] Step S3, transferring the homogeneous sol solution to a vacuum heating device, and performing vacuum nitrogen circulation at 60°C-80°C, heating the homogeneous sol solution to 130°C-150°C under nitrogen protection, slowly adding cesium oleate solution preheated to 130°C-150°C, maintaining the temperature and continuously stirring for 20min-40min to control the uniform generation of perovskite quantum dots in the silica network, and completing the sol-gel transition to form a stable SiO2@CsPbBr3 composite material;

[0009] Step S4, transfer the gel solution generated in step S3 to a supercritical CO2 drying device, set the temperature to 60-80°C and the pressure to 8-10Mpa; maintain it under supercritical conditions for 30min-120min to promote the formation of silica aerogel and the encapsulation of quantum dots; after drying and encapsulation, gradually lower the device temperature to room temperature, and then take the material out of the device.

[0010] In a specific embodiment, the aerogel particle size ranges from 10 nm to 100 nm.

[0011] In a specific embodiment, the aerogel particle size ranges from 10nm to 30nm, and the aerogel particle size is formed by reducing the tetraethyl orthosilicate (TEOS) concentration, increasing the ethanol ratio, reacting under acidic conditions (pH<7), and using a lower concentration of catalyst to form the silica aerogel with a particle size of 10nm-30nm.

[0012] In a specific embodiment, the aerogel particle size ranges from 30nm to 60nm, and the aerogel particle size is formed by reacting the silica aerogel with a particle size of 30nm to 60nm by a moderate tetraethyl orthosilicate (TEOS) concentration, a moderate ethanol ratio, under neutral conditions (pH=7), and using a moderate concentration of catalyst.

[0013] In a specific embodiment, the aerogel particle size ranges from 60nm to 100nm, and the aerogel particle size is formed by a higher concentration of tetraethyl orthosilicate (TEOS), an increased proportion of water, a reaction under alkaline conditions (pH>7), and a higher concentration of a catalyst to form the silica aerogel with a particle size of 60nm-100nm.

[0014] In a specific embodiment, in the step S2, the stirring temperature of the sol solution is 60° C., and the stirring time of the sol solution is 30 min.

[0015] In a specific embodiment, in step S3, the mixed sol is heated to 140° C. under nitrogen protection, and a cesium oleate solution preheated to 140° C. is slowly added.

[0016] In a specific embodiment, it is characterized in that, in the step S4, the process time of the silica aerogel formation and quantum dot encapsulation is 60 minutes.

[0017] In a second aspect of the present invention, a composite material of perovskite quantum dots and silica aerogel for synchronously generating color conversion is provided, which is prepared by any one of the preparation methods provided in the first aspect.

[0018] Beneficial effects of the present invention: 1) The innovation of this patent is that SiO2@CsPbBr3 is generated by synchronous sol-gel method and quantum dot generation technology, thereby preparing a composite material with excellent photoelectric performance and stability. This method avoids the complex process and stability problems caused by traditional step-by-step synthesis. In addition, by optimizing the supercritical drying and post-processing steps, they are merged into a unified processing process to improve process efficiency and material performance. 2) In terms of process, a one-step method is adopted to achieve the generation of SiO2@CsPbBr3 through synchronous sol-gel method and quantum dot generation technology, simplify the process and improve production efficiency. Due to the use of sol-gel method and quantum dot synchronous generation technology, perovskite quantum dots are generated in situ on the silica aerogel skeleton, reducing the problems of quantum dot agglomeration and degradation in the two-step process. At the same time, it can maintain high quantum yield and narrow-band luminescence characteristics, significantly improving the light efficiency and color expression of the display. In the present invention, silica aerogel provides physical isolation, significantly improves the environmental and thermal stability of quantum dots, and extends the service life of the material. In addition, the high transparency and low scattering properties of the composite material significantly improve the optical uniformity of the composite material, reduce optical loss, and improve display brightness and contrast. 3) Supercritical CO2 drying can effectively remove the solvent under high temperature and pressure to form a uniform aerogel structure while encapsulating perovskite quantum dots. This step itself has the effect of separation and purification, making the combination of quantum dots and aerogel more stable, thereby reducing the need for centrifugal treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic flow chart of a method for preparing a composite material of perovskite quantum dots and silica aerogel for synchronously generating color conversion provided in Example 1. DETAILED DESCRIPTION

[0020] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0021] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a composite material of perovskite quantum dots and silica aerogel for synchronously generating color conversion, comprising:

[0022] Step S1, dissolving cesium bromide and lead bromide in anhydrous N,N-dimethylformamide, and stirring until completely dissolved to prepare an initial quantum dot precursor solution; adding oleic acid and aminopropyltriethoxysilane to the initial quantum dot precursor solution, and obtaining a uniform precursor solution by ultrasonic oscillation;

[0023] Step S2, taking tetraethyl orthosilicate (TEOS) as a silicon source, mixing tetraethyl orthosilicate (TEOS) and a precursor solution, and rapidly stirring at the same time to form a preliminary SiO2@CsPbBr3 sol solution; stirring the sol solution at 50°C-70°C for 20min-60min to promote sol-gel transformation; slowly adding anhydrous ethanol, slowly dropping ammonia water and continuing to stir fully, detecting the pH value of the solution in real time, and gradually adjusting the pH to 6.5-7.5 to form a uniform homogeneous sol solution;

[0024] Step S3, transferring the homogeneous sol solution to a vacuum heating device, and performing vacuum nitrogen circulation at 60°C-80°C, heating the homogeneous sol solution to 130°C-150°C under nitrogen protection, slowly adding cesium oleate solution preheated to 130°C-150°C, maintaining the temperature and continuously stirring for 20min-40min to control the uniform generation of perovskite quantum dots in the silica network, and completing the sol-gel transition to form a stable SiO2@CsPbBr3 composite material;

[0025] Step S4, transfer the gel solution generated in step S3 to a supercritical CO2 drying device, set the temperature to 60-80°C and the pressure to 8-10Mpa; maintain it under supercritical conditions for 30min-120min to promote the formation of silica aerogel and the encapsulation of quantum dots; after drying and encapsulation, gradually lower the device temperature to room temperature, and then take the material out of the device.

[0026] Optionally, the aerogel particle size ranges from 10 nm to 100 nm.

[0027] According to actual needs, optionally, the aerogel particle size range is 10nm-30nm, and the aerogel particle size is formed by reducing the tetraethyl orthosilicate (TEOS) concentration, increasing the ethanol ratio, reacting under acidic conditions (pH<7), and using a lower concentration of catalyst to form the silica aerogel with a particle size of 10nm-30nm.

[0028] According to actual needs, optionally, the aerogel particle size range is 30nm-60nm, and the aerogel particle size is formed by reacting the silica aerogel with a particle size of 30nm-60nm under neutral conditions (pH=7) with a moderate tetraethyl orthosilicate (TEOS) concentration, a moderate ethanol ratio, and a moderate concentration of catalyst.

[0029] According to actual needs, optionally, the aerogel particle size range is 60nm-100nm, and the aerogel particle size is formed by higher tetraethyl orthosilicate (TEOS) concentration, increasing the proportion of water, reacting under alkaline conditions (pH>7), and using a higher concentration of catalyst to form the silica aerogel with a particle size of 60nm-100nm.

[0030] Typically, in this embodiment, in step S2, the stirring temperature of the sol solution is 60° C., and the stirring time of the sol solution is 30 min.

[0031] Typically, in this embodiment, in step S3, the mixed sol is heated to 140° C. under nitrogen protection, and a cesium oleate solution preheated to 140° C. is slowly added.

[0032] Typically, in this embodiment, in step S4, the process time for forming the silica aerogel and encapsulating the quantum dots is 60 minutes.

[0033] The following is further discussed with specific examples.

[0034] In the first embodiment of the present invention, the following steps are specifically included:

[0035] 1. Raw material preparation

[0036] Take 10ml tetraethyl orthosilicate (TEOS) as the silicon source. Weigh 0.2g cesium bromide (CsBr) and 0.3g lead bromide (PbBr2), dissolve in 10ml anhydrous N,N-dimethylformamide (DMF), stir until completely dissolved, and prepare the initial quantum dot precursor solution. Add 0.1g oleic acid and 0.1g 3-aminopropyltriethoxysilane (APTES) to the initial quantum dot precursor solution, and ultrasonically vibrate for 30min to obtain a uniform precursor solution.

[0037] 2. Synchronous sol-gel and quantum dot generation process

[0038] Mix TEOS and the precursor solution while stirring rapidly to form a preliminary SiO2@CsPbBr3 sol solution. Stir the sol solution at 60°C for 30 minutes to promote the sol-gel transition. Slowly add 10 ml of anhydrous ethanol to ensure anhydrous operation throughout the process. Use a pipette to slowly add a small amount of ammonia water (concentration of 25%), stir thoroughly after each addition and check the pH value of the solution, and gradually adjust it to 7.0 to form a uniform homogeneous sol solution.

[0039] Transfer to a three-necked flask, circulate vacuum nitrogen at 60-80°C, heat the homogeneous sol solution to 140°C under nitrogen protection, and slowly add 2 ml of cesium oleate solution preheated to 140°C. Continue stirring at 140°C for 30 minutes to ensure that the perovskite quantum dots are uniformly generated in the silica network and the sol-gel transition is completed to form a stable SiO2@CsPbBr3 composite material.

[0040] 3. Unified drying and post-processing

[0041] Transfer the above gel solution to a supercritical CO2 drying device, set the temperature to 60-80°C and the pressure to 8-10Mpa. Keep it under supercritical conditions for 1 hour (to ensure that the perovskite quantum dots will not fail, use critical CO2 drying to replace the perovskite quantum dots for annealing) to ensure the formation of silica aerogel and the encapsulation of quantum dots, while avoiding damage to the quantum dots by long-term treatment. Since supercritical CO2 drying can be carried out at relatively low temperatures, supercritical drying and heat treatment can be combined. After drying and encapsulation are completed, the equipment temperature is gradually lowered to room temperature, and then the material is removed from the equipment.

[0042] It is worth mentioning that after supercritical drying, the perovskite quantum dots in the silica aerogel no longer have any reaction solution and cannot be generated through post-processing. Therefore, the generation of perovskite quantum dots should be completed before supercritical drying.

[0043] In a second embodiment of the present invention, a composite material of perovskite quantum dots and silica aerogel for simultaneous color conversion is provided, which is prepared by the preparation method provided in the first embodiment.

[0044] Innovations and advantages of the present invention

[0045] The present invention generates SiO2@CsPbBr3 by synchronous sol-gel method and quantum dot generation technology, thereby preparing a composite material with excellent photoelectric performance and stability. The method avoids the complex process and stability problems caused by traditional step-by-step synthesis. In addition, by optimizing the supercritical drying and post-processing steps, they are combined into a unified processing process to improve process efficiency and material performance.

[0046] In addition, the present invention has the following advantages:

[0047] Synchronous synthesis: SiO2@CsPbBr3 is generated through synchronous sol-gel method and quantum dot generation technology, which simplifies the process and improves production efficiency.

[0048] High quantum yield and narrow-band luminescence: Perovskite quantum dots are generated on a silica aerogel skeleton, maintaining high quantum yield and narrow-band luminescence characteristics, significantly improving the light efficiency and color expression of the display.

[0049] Environmental and thermal stability: Silica aerogel provides physical isolation, significantly improving the environmental and thermal stability of quantum dots and extending the service life of the material.

[0050] Optimization of optical uniformity: The high transparency and low scattering properties of the composite material significantly improve the optical uniformity of the composite material, reduce optical loss, and increase display brightness and contrast.

[0051] In addition, the role of supercritical drying is that supercritical CO2 drying can effectively remove the solvent under high temperature and pressure to form a uniform aerogel structure while encapsulating perovskite quantum dots. This step itself has the effect of separation and purification, making the combination of quantum dots and aerogel more stable, thereby reducing the need for centrifugal treatment.

[0052] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a composite material of perovskite quantum dots and silica aerogel for synchronous color conversion, characterized in that: The method comprises: Step S1, dissolving cesium bromide and lead bromide in anhydrous N,N-dimethylformamide, and stirring until completely dissolved to prepare an initial quantum dot precursor solution; adding oleic acid and aminopropyltriethoxysilane to the initial quantum dot precursor solution, and obtaining a uniform precursor solution by ultrasonic oscillation; Step S2, taking tetraethyl orthosilicate (TEOS) as a silicon source, mixing tetraethyl orthosilicate (TEOS) and a precursor solution, and rapidly stirring at the same time to form a preliminary SiO2@CsPbBr3 sol solution; stirring the sol solution at 50°C-70°C for 20min-60min to promote sol-gel transformation; slowly adding anhydrous ethanol, slowly dropping ammonia water and continuing to stir fully, detecting the pH value of the solution in real time, and gradually adjusting the pH to 6.5-7.5 to form a uniform homogeneous sol solution; Step S3, transferring the homogeneous sol solution to a vacuum heating device, and performing vacuum nitrogen circulation at 60°C-80°C, heating the homogeneous sol solution to 130°C-150°C under nitrogen protection, slowly adding cesium oleate solution preheated to 130°C-150°C, maintaining the temperature and continuously stirring for 20min-40min to control the uniform generation of perovskite quantum dots in the silica network, and completing the sol-gel transition to form a stable SiO2@CsPbBr3 composite material; Step S4, transfer the gel solution generated in step S3 to a supercritical CO2 drying device, set the temperature to 60-80°C and the pressure to 8-10Mpa; maintain it under supercritical conditions for 30min-120min to promote the formation of silica aerogel and the encapsulation of quantum dots; after drying and encapsulation, gradually lower the device temperature to room temperature, and then take the material out of the device.

2. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 1, characterized in that: The aerogel particle size ranges from 10 nm to 100 nm.

3. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 2, characterized in that: The aerogel particle size ranges from 10nm to 30nm. The aerogel particle size is formed by reducing the tetraethyl orthosilicate (TEOS) concentration, increasing the ethanol ratio, reacting under acidic conditions (pH<7), and using a lower concentration of catalyst to form the silica aerogel with a particle size of 10nm-30nm.

4. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 2, characterized in that: The aerogel particle size ranges from 30nm to 60nm. The aerogel particle size is formed by reacting a moderate tetraethyl orthosilicate (TEOS) concentration, a moderate ethanol ratio, under neutral conditions (pH=7), and using a moderate concentration of a catalyst to form the silica aerogel with a particle size of 30nm-60nm.

5. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 2, characterized in that: The aerogel particle size ranges from 60nm to 100nm. The aerogel particle size is formed by increasing the tetraethyl orthosilicate (TEOS) concentration, increasing the proportion of water, reacting under alkaline conditions (pH>7), and using a higher concentration of catalyst to form the silica aerogel with a particle size of 60nm-100nm.

6. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 1, characterized in that: In the step S2, the stirring temperature of the sol solution is 60° C., and the stirring time of the sol solution is 30 min.

7. A method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 1, characterized in that: In step S3, the mixed sol is heated to 140° C. under nitrogen protection, and a cesium oleate solution preheated to 140° C. is slowly added.

8. The method for preparing a composite material of perovskite quantum dots and silica aerogel for color conversion synchronous generation according to claim 1, characterized in that: In step S4, the process time for forming the silica aerogel and encapsulating the quantum dots is 60 minutes.

9. A composite material of perovskite quantum dots and silica aerogel for synchronous color conversion, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.